Advantages and disadvantages of the unification of rules simplifying cross-border debt collection - Jesús Bores Lazo (LeXonomica, 2021)
In the period when the Directorate-General Justice, Freedom and Security  (since July 1, 2010 has become two directorates – Directorate-General for Justice and Directorate-General for Home Affairs) was only a »Task Force« and one single EU official – Anne Marie Rouchaud - was in charge of cooperation in civil and commercial matters, were always existing very highexpectations in the process of building the European Area of Justice and developing legal instruments to facilitate the right of the individuals all over Europe through Private Law. Not even 15 years ago, we could find a declared Vasque Terrorist criminally convicted by the Spanish authorities buying in the Belgian grocery store; while marriage was easily and widely recognized in all jurisdictions, divorce, separation, and nullity of marriages caused great headaches both for the couple and the lawyers in all Member States, and being paid by a debtor abroad was a dream really celebrated when, if any time, happened. By the way, it never happened with minor claims ...